Penyatuan Zona Waktu Indonesia dan Implikasinya Pada Waktu Ibadah - Ahmad Junaidi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
˜Indonesian economical development extensive and speedy committee’ (KP3EI), at March 12 2012, unifies Indonesia zones which is now divided into three parts. These three time zone divisions, according to KP3EI, affect amount aspect of entities inefficiency. This paper tries both to elaborate implications that the unification effects to praying zones of Moslem community and to seek an alternative formulae for ideal time zone of Indonesian Republic (NKRI). The writer sees that the idea of those three zone unifications will affect salat time schedule reduction up to an hour for territories base on western Indonesian time zone ”˜WIB’ (GMT +7) and vice versa for territories base on eastern Indonesian time zone ”˜WIT’ (GMT ”“9). The territories base on central Indonesian time zone ”˜WITA (GMT +8) is fixed due to its own base. The change from ”˜WIB’ and ”˜WIT’ to ”˜WITA’ +8 is to effect second calculation results; but because that change value does not reach a second that can probably be neglected. The ideal zone of Indonesian territories, according to writer, relates not only to ”˜religious’ activities but also to work activities. so that the three time zone divisions are the only solution.